2005
DOI: 10.1111/j.1537-2995.2005.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Further evaluation of a new standard of efficacy for stored platelets

Abstract: Apheresis PLTs stored for 7 days met the criterion proposed for comparison with fresh PLTs. This analytic approach is feasible with PLTs collected and prepared via a manual method. A standardized protocol for radiolabeling PLTs with 51Cr and 111In and analyzing the results in a standardized fashion was employed successfully, with the two radioisotopes yielding similar results. The importance of correcting for residual activity after disappearance of injected cells was noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 10 publications
3
33
0
Order By: Relevance
“…Because of small numbers, none of these site or radiolabel differences achieved significance. Similarly, in another apheresis study, no differences were observed in the results based on the radiolabel used for the fresh and stored PLT studies 18 …”
Section: Discussionmentioning
confidence: 83%
“…Because of small numbers, none of these site or radiolabel differences achieved significance. Similarly, in another apheresis study, no differences were observed in the results based on the radiolabel used for the fresh and stored PLT studies 18 …”
Section: Discussionmentioning
confidence: 83%
“…This is currently the most widely used model for the interpretation of clinical data [7], [17], [18], [19], [20], [21], [22]. Unlike random and lifespan-dependent consumption, this model is not supported by any well characterized physical process, and a model based solely on lifespan-dependent platelet consumption demonstrates a better fit to in vivo platelet consumption data [5].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report in vitro effects of platelet storage for up to 9 days, comparing PO‐80 with another polyolefin, PL2410 (Baxter Healthcare, Deerfield, IL, USA). Next, to assess the clinical utility of PO‐80, we recruited healthy volunteers to compare in vivo survival and recovery of autologous platelets stored in PO‐80 for 7 days with fresh platelets manually separated from whole blood [8] and radiolabelled with either 111 In or 51 Cr. This is one of only a few platelet studies to date in which the Murphy method [9] has been properly executed, analysed and reported.…”
Section: Introductionmentioning
confidence: 99%